Modified Embedded‐Atom Method Potentials for the Plasticity and Fracture Behaviors of Unary HCP Metals. Issue 1 (1st December 2021) - Chen, Shuai; Aitken, Zachary H.; Sorkin, Viacheslav; Yu, Zhi Gen; Wu, Zhaoxuan; Zhang, Yong‐Wei
Abstract: Modified embedded‐atom method (MEAM) potentials have been widely used in molecular dynamics (MD) simulations to describe the interatomic interactions in metallic systems. However, conventional MEAM potentials are almost exclusively fit to a limited number of key single‐value properties, limiting the predictability of MD simulations, especially for complex hexagonal‐close‐packed (HCP) metals with multiple slip systems. Here, three MEAM potentials for unary HCP metals (Mg, Co, and Ti) are fit to conventional target properties, as well as continuous‐energy curves and their gradients obtained from density‐functional theory calculations. These targets include the lattice parameters, cohesive energy, elastic constants, and surface energies as well as the cohesive energy curve, basal plane decohesion energy curve, and generalized stacking fault energy curves for basal, prismatic, pyramidal I, and pyramidal II planes. These interatomic potentials demonstrate excellent reproduction of relevant properties and enable accurate MD simulations of volumetric and plastic deformations, as well as fracture in Mg, Co, and Ti HCP metals. Importantly, the interatomic potentials demonstrate better performance than all existing EAM/MEAM potentials readily available from the literature. Abstract : Three modified embedded‐atom method potentials for unary HCP metals (Mg, Co, and Ti) are fit to conventional target properties, continuous‐energy curves, and their gradients obtained from density‐functional theory calculations. These interatomic potentials demonstrate excellent reproduction of relevant properties and enable accurate molecular dynamics simulations of volumetric and plastic deformations, as well as fracture in Mg, Co, and Ti metals.